2015
DOI: 10.1186/s12874-015-0098-7
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup identification for treatment selection in biomarker adaptive design

Abstract: BackgroundAdvances in molecular technology have shifted new drug development toward targeted therapy for treatments expected to benefit subpopulations of patients. Adaptive signature design (ASD) has been proposed to identify the most suitable target patient subgroup to enhance efficacy of treatment effect. There are two essential aspects in the development of biomarker adaptive designs: 1) an accurate classifier to identify the most appropriate treatment for patients, and 2) statistical tests to detect treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Based on these data sets, three different classification algorithms (diagonal linear discriminant analysis (dLDA) [ 19 , 20 ], k-nearest neighbors (K-NN) [ 20 , 21 ] and support vector machines (SVM) with linear kernel [ 22 , 23 ] were generated and tested. In order to formulate and select the best model for classification of LB, the misclassification rate for each classifier was estimated using leave-one-out cross-validation (LOOCV), during which we applied uni-variate t-tests with a grit of p-values (p < 0.001, p < 0.005, p < 0.01, p < 0.05) for selection of the optimal number of probe sets to include in each model.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these data sets, three different classification algorithms (diagonal linear discriminant analysis (dLDA) [ 19 , 20 ], k-nearest neighbors (K-NN) [ 20 , 21 ] and support vector machines (SVM) with linear kernel [ 22 , 23 ] were generated and tested. In order to formulate and select the best model for classification of LB, the misclassification rate for each classifier was estimated using leave-one-out cross-validation (LOOCV), during which we applied uni-variate t-tests with a grit of p-values (p < 0.001, p < 0.005, p < 0.01, p < 0.05) for selection of the optimal number of probe sets to include in each model.…”
Section: Methodsmentioning
confidence: 99%
“…5,8,9 Subgroup analyses represent a valuable source of information, but implementation in (R)CTs may lead to challenges as well, such as the pre-specification of relevant patient characteristics and respective cut-off values for the definition of subgroups. [10][11][12] Previous knowledge Subgroup analyses were often criticised for spurious, meaningless or potentially misleading results. 2,5,[13][14][15] Previous reviews showed that reported information regarding the implementation of subgroup analyses in (R)CTs was not consistent or complete.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 8 , 9 Subgroup analyses represent a valuable source of information, but implementation in (R)CTs may lead to challenges as well, such as the pre-specification of relevant patient characteristics and respective cut-off values for the definition of subgroups. 10 12 …”
Section: Introductionmentioning
confidence: 99%
“…The Multiwfn program [34] was employed for the topological analysis of the electron density at the bond critical point (BCP) in the complex, performed using the Atoms In Molecule (AIM) theory, [35] the visualization of the TrB in complexes, performed by the interaction region indicator (IRI) [36] method, analysis of the role of orbitals in the complexes by the extended transition state‐natural orbitals for chemical valence (ETS‐NOCV) [37] method, and generation of the molecular electrostatic potentials (MEPs) [38] of the monomers. IRI was calculated with formulas of IRI()r=ρr[]ρ()ra ${IRI\left( r \right) = {{\left| {\nabla \rho \left( r \right)} \right|} \over {\left[ {\rho \left( r \right)} \right]^a }}}$ , where ρ is electron density.…”
Section: Computational Detailsmentioning
confidence: 99%